2020
DOI: 10.3390/nu12041027
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dense Salty Food Consumption Frequency Is Associated with Diastolic Hypertension in Spanish Children

Abstract: High blood pressure (BP) is a risk factor for cardiovascular disease and sodium consumption is related to high BP. Moreover, sugar-sweetened beverages (SSB) and the Dietary Approach to Stop Hypertension (DASH) influence BP. For this reason, we investigated whether: 1) children with risk of elevated BP had a higher consumption frequency (CF) of energy-dense salty foods (EDSF), high-sugary foods (HSF) and SSB or a low DASH score; and 2) children with a higher CF of EDSF showed a worse anthropometric and metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
1
11
0
1
Order By: Relevance
“…In addition, we also find the HC cluster associated with a worse lipid profile specifically in these subgroups, allowing us to suggest that the dietary pattern may less strongly influence a worse cholesterol metabolic profile than type of fat distribution (and physical activity levels) [57]. The SP cluster showed a worse CVD profile, indicated through higher DBP figures, when analyzed in the total population and the normal weight group, in agreement with a previous analysis carried out by our team, which identified a higher DBP in children with a higher consumption frequency of energy dense salty foods [58]. Additionally, the SP cluster was associated with a mainly worse metabolic phenotype through several biochemical indicators, both in the total sample and the age-gender-and BMI-stratified analyses.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we also find the HC cluster associated with a worse lipid profile specifically in these subgroups, allowing us to suggest that the dietary pattern may less strongly influence a worse cholesterol metabolic profile than type of fat distribution (and physical activity levels) [57]. The SP cluster showed a worse CVD profile, indicated through higher DBP figures, when analyzed in the total population and the normal weight group, in agreement with a previous analysis carried out by our team, which identified a higher DBP in children with a higher consumption frequency of energy dense salty foods [58]. Additionally, the SP cluster was associated with a mainly worse metabolic phenotype through several biochemical indicators, both in the total sample and the age-gender-and BMI-stratified analyses.…”
Section: Discussionsupporting
confidence: 87%
“…Dietary intake was assessed using a 93-item food frequency questionnaire based on a Spanish adaptation [25,26] of a previously validated instrument [27][28][29]. Questionnaires were administered at baseline and at 6 months during face-to-face visits with nutritionists to assess food habits during the preceding month.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…It was observed that an increase of one serving/day of sugar-sweetened beverages was associated with an increase of 0.8 mmHg in systolic blood pressure (95% CI: 0.4-1.2) and 0.3 (95% CI: 0.0-0.5) mmHg in diastolic blood pressure [28]. Pérez-Gimeno et al [29] observed that diastolic hypertension was associated with a higher frequency of consumption of salty foods (700 mg of sodium/100 g), such as pizza, chips, and sausages, in Spanish children aged 5-16 years, independent of nutritional status.…”
Section: Introductionmentioning
confidence: 98%